Absorption of starch by healthy ileostomates: effect of transit time and of carbohydrate load. - Chapman, R; Sillery, J; Graham, M; Saunders, DR (1985)
Recently, breath hydrogen studies and intubation techniques have indicated that in excess of 10% of starch in normal foods may be malabsorbed in the small intestine and enter the colon. We evaluated starch absorption in healthy subjects with ileostomy. First, unabsorbed starch was quantified in ileostomy effluent from six ileostomates who ingested constant diets of wheat and potato starch for four days. Daily unabsorbed starch ranged from 1.3% to 5.0% of total ingested starch. Second, starch from a radiolabeled solid meal containing 50 g potato starch was measured under control conditions and after altering transit time with either loperamide, or magnesium citrate. Loperamide significantly decreased the amount of unabsorbed starch in all six ileostomates (p less than 0.05), while magnesium citrate significantly increased starch malabsorption in all six subjects (p less than 0.05). Third, starch absorption was measured after single solid meals containing 25, 50, 75, and 100 g potato starch. There was a linear relationship between starch input and output. Mean output expressed as a percent of input remained constant. We conclude that the degree of starch malabsorption by the small intestine of ileostomates may be less than that estimated by indirect methods in intact humans. The amount of unabsorbed starch is directly related to the quantity ingested and to the small intestinal transit time.